Arranging response requirements and the distribution of reinforcers: A brief review of preference and performance outcomes. Issue 1 (4th October 2016) - Ward-Horner, John C.; Cengher, Mirela; Ross, Robert K.; Fienup, Daniel M.
Abstract : Recent research has demonstrated that some participants prefer to complete a larger series of responses in exchange for a longer duration of reinforcer access, rather than completing fewer tasks associated with smaller, but more frequent, reinforcer access. This review provides a summary of this line of research, examines variables contributing to participant preference and performance under different response‐reinforcer arrangements, and discusses limitations and areas for future research.